APPLICATION OF VIETA’S THEOREM TO GEOMETRY - Azimboy Ro‘zimboev Hamro o‘g‘li; Abduxalilov Fazliddin To‘lanboy o‘g‘li; Muhammadov Sherzod Shahobbidin o‘g‘li (World Scientific Research Journal, 2025)
Annotation: This paper explores the application of Vieta’s theorem in geometry, particularly in coordinate geometry, triangle centers, and intersection problems. By leveraging relationships between polynomial roots and coefficients, Vieta’s theorem simplifies geometric calculations and enhances problem-solving strategies in plane geometry.